Analisis Prioritas Pengembangan Kawasan Andalan Di Desa Karang Indah Kecamatan Mandastana - Nisa’ AS, Zumrotun; Nur, Muhammad Anshar (PPJP ULM, 2019)
The aims of this research are to (1) Find out how the contribution of each criterion to the development of a mainstay area In The Karang Indah (2) to find out the potential of what is a priority to be developed into a mainstay in the village of Karang Indah districts of Mandastana. The respondents of this research are ten, which are considered to influence the mainstay's determination in the Village of Karang Indah districs of Mandastana, which can be used in the data processing. Data is processed by using AHP (Analytical Hierarchy Process). The result of this research showed that the alternative criteria of the regional potential, regional policy, per capita income, and employment opportunities influence the determined priority of mainstay area development, by the value of preference in order are 54% regional potential, 23% of local policy, 14% per capita income, and 9% of employment opportunities. Based on the alternatives criteria, the priority development area mainstay selection is 58% horticulture of orange plants, a combination or Agro-education 30% and 12% of English-Village. This research concludes that the most dominant sector is the horticulture of oranges' plants (58%).